Translation to English, cross-cultural adaptation, and pilot testing of the self-report questionnaire on swallowing difficulties with medication intake and coping strategies (SWAMECO) for adults with polypharmacy. Issue 8 (16th August 2020) - Arnet, Isabelle; Messerli, Markus; Oezvegyi, Jana; Hersberger, Kurt; Sahm, Laura
Abstract : Objectives: To translate the SWAMECO from German into English; to complete content and face validity with healthcare professionals (HCPs) and with patients from the target population that is, community-dwelling adult patients taking three or more medicines for three or more months. Design: The process followed guidance from Sousa et al and included translation and cross-cultural adaptation, and cognitive testing among selected HCPs and patients. As the SWAMECO questionnaire is a screening instrument, pilot testing was performed in the target population. Setting: Three community pharmacies in and around Cork (Ireland) recruited patients for interviews and pilot testing. Participants: Community-dwelling patients with ≥3 oral medications for ≥3 months, aged ≥18 years. Outcome measures: Answers to the SWAMECO questionnaire; clarity of each question, each instruction and each response format. Results: Issues related to cultural and conceptual differences were resolved by rewording some items. Ten HCPs and 11 patients completed the questionnaire and gave their feedback and opinions on criteria according to Fitzpatrick et al . Revisions included rewording; deleting of two questions; using of colour to signpost that is, where to skip questions that were not applicable to the participants; and replacement of the A-14 medication adherence scale with three validated items. Of the 66 patients enrolled for pilot testing, eight (12.1%) indicated swallowing difficulties. Difficulties with ingesting foods or liquids correlated with swallowing difficulties (p=0.001). All patients perceived discomfort (mean 6.9 on a Visual Analogue Scale from 0 to 10). Patients with swallowing difficulties were significantly more likely to report modifying their medicines (p=0.004) and having poorer medication adherence (p=0.028) than those who had no swallowing difficulties. Conclusions: The version of the SWAMECO questionnaire in English contains 28 items and is ready for use in adults with polypharmacy.